Transformational Leadership: Lessons from Ramosilei’s Leadership Study in the Vhembe District, Limpopo Province, South Africa - Musitha, Mavhungu Elias (International Journal of Educational Development in Africa, 2018)
<span style="font-family: 'Times New Roman',serif; font-size: 11pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: HE; mso-bidi-font-size: 12.0pt;" lang="EN-GB">Educators are faced with classroom problems in South African schools which force them to quit as they cannot find solutions to them. This study investigated whether there were lessons to be learned from a successful study by a retired school teacher in the former Venda in Limpopo Province of South Africa. A qualitative approach was adopted to explain and describe the study. Data was obtained from both primary sources such as speeches where the researcher took down notes during the interview proceedings and also from secondary data extracted from literature. From the notes taken by the researcher, information was collated and analysed to answer the research questions. This study has revealed that learning and teaching should be integrated in the classroom and the teacher should provide leadership all the time and understand that learners are not small adults but children who need an adult to take them by the hand and guide them towards adulthood. This study recommends that the lessons from Ramosilei should be shared with other schools. It also proposes that schools could succeed if they establish stakeholder relationships with the management and administration of schools.